Domestic Environmental Factors Associated with Pediatric Snoring: A Scoping Review Protocol - Supriatin, Supriatin; Wahyuni, Nuniek Tri; Widadi, Sri Yekti; Nurhaeni, Heni; Anitasari, Silvia (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Since one-third of children who snore consistently may have OSAS, understanding the causes is vital. Preventing snoring requires addressing obesity, allergies, and anatomical anomalies. Indoor allergens and enlarged tonsils and adenoids may also cause youngsters to snore. The review aims to identify and categorize key concepts, types of evidence, and research gaps in this area.  The scoping review will follow the methodology and stages outlined by the Joana Briggs Institute ((JBI). The final output will follow the PRISMA-Protocols (PRISMA-P) 2015 checklist. This review serves as a necessary step before conducting a systematic review and clinical studies. Childhood snoring is a common problem that can have adverse effects on a child’s health and well-being. It is importing ant for parents to understand the hazards of snoring and seek support if they suspect their child may have a sleep disorder. Treatment options vary depending on the cause and severity of snoring, and may include lifestyle changes, medication, or surgery. More research is need to better understand the relationship between environmental factors and snoring children, including the impact of pollutant such as NO2 and passive smoking. Early detection and treatment of snoring in children is crucial, as if can have long-term effects on their health and well-being. The conclusion is that knowledge empowers parents to take the necessary steps to ensure the well-being and healthy sleep of their children.